2003
DOI: 10.1073/pnas.2433165100
|View full text |Cite
|
Sign up to set email alerts
|

Viral protein U counteracts a human host cell restriction that inhibits HIV-1 particle production

Abstract: Human cells resist viral infections by a variety of mechanisms.Viruses must overcome host cell restrictions to successfully reproduce their genetic material. Here, we identify a host restriction to viral replication that acts at the stage of particle assembly. Viral protein U (Vpu) is an HIV-1 accessory protein that enhances particle assembly and release in most human cells, but not in simian cells. By using human-simian cell heterokaryons, we show that the inhibition of assembly in human cells is dominant. Vp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
149
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 34 publications
7
149
1
1
Order By: Relevance
“…HIV‐1 Viral protein U (Vpu) 59, 60 is renowned for its role in proteasomal degradation of CD4 61, 62 and enhancement of HIV‐1 release from infected cells 63, 64, 65 in a cell type‐dependent manner 66. In 2008, two independent laboratories showed that cell type‐specific expression of BST‐2 correlates with Vpu‐dependent release of HIV‐1.…”
Section: Viral Antagonists Of Bst‐2 and Neutralization Of Bst‐2 Antivmentioning
confidence: 99%
“…HIV‐1 Viral protein U (Vpu) 59, 60 is renowned for its role in proteasomal degradation of CD4 61, 62 and enhancement of HIV‐1 release from infected cells 63, 64, 65 in a cell type‐dependent manner 66. In 2008, two independent laboratories showed that cell type‐specific expression of BST‐2 correlates with Vpu‐dependent release of HIV‐1.…”
Section: Viral Antagonists Of Bst‐2 and Neutralization Of Bst‐2 Antivmentioning
confidence: 99%
“…Experimental evidence has also been obtained that Vpu enhances viral budding by interfering with the endogenous potassium channel TASK-1, 34 with sequence homology suggesting that HIV-1 Vpu may have evolved from the Nterminal TM domain of TASK-1 and may function by forming hetero-oligomers with TASK-1 in host cell membranes. Recent experiments indicate that Vpu facilitates viral budding through interactions with host cell proteins that otherwise inhibit viral budding, 35 in particular an integral membrane protein dubbed tetherin, CD317, or BST-2. 36,37 Tetherin tethers budding virions to host cells by linking the viral and host cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of Vpu to increase progeny virus secretion from infected cells had been attributed initially to ion conductive membrane pore formation characteristic to cells over-expressing Vpu [8]. However, a later report [9] showed that the requirement for Vpu is host…”
Section: Viral Protein U (Vpu)mentioning
confidence: 99%